Biomimetic multifunctional nanozymes enhanced radiosensitization for breast cancer via an X-ray triggered cascade reaction. Issue 19 (19th April 2022) - Yang, Lin; Du, Xiao; Qin, Yanru; Wang, Xueyuan; Zhang, Liefeng; Chen, Zhimeng; Wang, Zhongjie; Yang, Xu; Lei, Meng; Zhu, Yongqiang
Abstract : Design and manufacture of an ultra-small bionic multifunctional nanozyme BSA@CNP/Fe 2+  as a radiosensitizer to treat breast cancer. Abstract : Radiotherapy has been widely applied for breast cancer treatment in the clinic, while improving the radiation sensitivity of tumors and protecting normal tissues from radiation damage has drawn considerable attention. In this study, we reported a biomimetic multifunctional nanozyme (BSA@CeO/Fe 2+ ), which can be used as a radiosensitizer for breast cancer treatment. It was demonstrated that BSA@CeO/Fe 2+ presented a pH dependent multiple enzyme like activity that enhances the hydroxyl radical level by cascade catalytic reactions in a tumor microenvironment to obtain a desirable tumor-suppression rate (83.07%). Moreover, BSA@CeO/Fe 2+ was also proved to reduce reactive oxygen species levels in normal cells. Additionally, BSA@CeO/Fe 2+ nanozymes showed no obvious toxicity by routine blood examination and blood biochemistry assays. Therefore, this work provided a promising strategy for nanocatalytic tumor therapy by rationally designing biomimetic nanozymes with multienzymatic activities for achieving high radiotherapy efficacy and excellent biosafety simultaneously.